2014
DOI: 10.1016/j.freeradbiomed.2013.12.026
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol protects liver from binge alcohol-induced steatosis by mechanisms including inhibition of oxidative stress and increase in autophagy

Abstract: Acute alcohol drinking induces steatosis, and effective prevention of steatosis can protect liver from progressive damage caused by alcohol. Increased oxidative stress has been reported as one mechanism underlying alcohol-induced steatosis. We evaluated whether cannabidiol, which has been reported to function as an antioxidant, can protect the liver from alcohol-generated oxidative stress-induced steatosis. Cannabidiol can prevent acute alcohol-induced liver steatosis in mice, possibly by preventing the increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
99
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(106 citation statements)
references
References 40 publications
3
99
0
Order By: Relevance
“…Modulation of autophagy was considered to be an effective approach to alleviate liver injury (26)(27)(28). In the current study we have evaluated the effect of GCM on autophagy induction and showed that GCM caused a significant induction of 19 autophagy.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Modulation of autophagy was considered to be an effective approach to alleviate liver injury (26)(27)(28). In the current study we have evaluated the effect of GCM on autophagy induction and showed that GCM caused a significant induction of 19 autophagy.…”
Section: Discussionmentioning
confidence: 83%
“…It has been shown that autophagy induction can reduce alcohol-induced hepatotoxicity possibly associated with removing damaged mitochondria and accumulated lipid droplets (26)(27)(28). We next asked if autophagy was also involved in Quantitative analysis of LC3-puncta-positive cells showed that the number of cells with LC3 puncta in GCM-treated cells was significantly increased compared with the 16 untreated control (Fig 7C).…”
Section: Gcm Activates Autophagymentioning
confidence: 90%
“…Additionally, both compounds activate and desensitize the transient receptor potential vanilloid type-1 (TRPV1) channel [9], an emerging target in obesity and related cardiometabolic risk factors [10]. Importantly, CBD inhibits weight gain in rats on high-fat diets and the development of alcohol-induced hepatosteatosis in mice [11,12], whereas THCV improves insulin sensitivity and decreases triglyceride (TG) accumulation within the livers of obese mice [13]. THCV was recently shown to reduce insulin resistance and hypertension in a small double blind placebo-controlled clinical trial in type 2 diabetes patients with dyslipidemia [14].…”
Section: Introductionmentioning
confidence: 99%
“…Although CBD is considered a biologically inactive molecule (11,12), it was reported to exert cytoprotective effects in various preclinical models and was shown to be safe in patients (13). Several preclinical studies described the protective effect of CBD in diseases associated with increased oxidative stress, inflammation and cell death such as in colitis (14), diabetic complications (15), drug-induced nephrotoxicity (16), alcohol-induced steatohepatosis (17) remodeling. Fibrotic area was quantified using ImageJ software (NIH).…”
Section: Induction Of Eam and Experimental Groupsmentioning
confidence: 99%